Taking the First Full Drink: Epidemiological Evidence on Male–Female Differences in the United States. (April 2016) - Cheng, Hui G.; Cantave, Marven D.; Anthony, James C.
Abstract : Background: This research extends prior epidemiological estimates for the United States and re‐examines a previously described male excess in alcohol drinking. Its aim was to estimate fine‐grained age‐specific incidence of becoming a drinker among 12‐ to 24‐year‐old U.S. males and females, and to compare incidence estimates with prevalence proportions. Methods: The study population is 12‐ to 24‐year‐old noninstitutionalized U.S. civilian residents. Estimates are from 12 successive U.S. National Surveys on Drug Use and Health (NSDUH), with nationally representative samples drawn each year from 2002 to 2013 and assessed via computer‐assisted self‐interviews ( n  ~ 390, 000). Analysis‐weighted incidence and prevalence estimates are generated using the NSDUH Restricted Data Analysis System for 6 year‐pairs. Meta‐analysis‐derived summary estimates are provided, treating each year‐pair as a replication. Results: In this 21st century evidence, there no longer is male excess of incidence with respect to underage drinking. Indeed, in mid‐adolescence, there is a clear female excess for the risk of becoming an underage drinker. Meta‐analytic summaries disclosed no other male–female differences in incidence. Nevertheless, a male excess in the prevalence of recently active drinking can be seen after the age of 19 years. Conclusions: This new evidence from the United States shows that the so‐called "gender gap" in risk of becoming a drinker has narrowed to the point of there being no gap at all. Indeed, in mid‐adolescence, risk of starting to drink is greater for females than for males. Abstract : In the twenty‐first‐century United States, there is a clear female excess for the risk of becoming an underage drinker in mid‐adolescence. Male–female parity is seen for the other adolescents and young adults in these nationally representative samples. This new evidence shows that the "gender gap" in risk of becoming a drinker has narrowed to the point of there being no gap at all. Indeed, in mid‐adolescence, the risk of becoming an underage drinker is greater for females than for males.